تطوير التدريب الزراعي في الدول العربية - أ.د. رياض شعبان لملوم; د.عبدالسلام أحمد كريميد (Aljameai, 2025)
المستخلص:تناولت الورقة البحثية دراسة وتحليل واقع التدريب الزراعي في الدول العربية ودوره في تعزيز التنمية الزراعية وتحليل ومناقشة أهم المعوقات لإدارية والفنية التي تحول دون الرفع من كفاءة التدريب الزراعي في رفع كفاءة العاملين بالقطاع الزراعي والأنشطة الزراعية المختلفة، وقد تم استعراض الجوانب النظرية ومفاهيم التدريب والياته وتحليل وتقييم واقع التدريب الزراعي باستخدام التحليل الوصفي لواقع التدريب الزراعي ومؤشراته وعلاقته بالتنمية الزراعية. وأوضحت نتائج البحث أن التدريب الزراعي في الدول العربية لازال يعاني من القصور في مواجهة متطلبات رفع الكفاءة الفنية للعاملين في المجال الزراعي نتيجة عدد من المعوقات الإدارية والفنية التي حالت دون تطوير التعليم الزراعي، وقد توصلت الورقة إلى اقتراح عدد من التوصيات التي يمكن أن تساهم من رفع كفاءة التدريب الزراعي في الدول العربية.Abstract:This paper examines and analyzes the current state of agricultural training in Arab countries and its role in promoting agricultural development. It discusses the major administrative and technical constraints that hinder the effectiveness of training programs in enhancing the skills and competencies of workers in the agricultural sector and its various activities.The study reviews the theoretical foundations of training, its concepts and significance, and provides an assessment of the existing agricultural training systems through a descriptive analysis of their status, indicators and linkages to agricultural development.The findings reveal that agricultural training in Arab countries continues to face significant shortcomings in meeting the requirements of improving the technical efficiency of agricultural workers. This is largely due to persistent administrative and technical obstacles, coupled with the absence of well-formulated training policies capable of overcoming these challenges.In light of these findings, the paper proposes several recommendations aimed at enhancing the efficiency and impact of agricultural training, thereby contributing to agricultural development across the Arab region.